Comparison between artificial turf and natural grass on agility and speed among female hockey players of SMK Seberang Temerloh / Wan Amirul Syafiq Wan Rosli - Wan Rosli, Wan Amirul Syafiq (Faculty of Sports Science And Recreation, 2019)
The purpose of this study was to investigate the comparison two different surfaces which are artificial turf and natural grass on speed and agility among female player hockey team of SMK Seberang Temerloh, Pahang. Several players from SMK Seberang Temerloh(n=20) were selected as the sample of the study using purposive sampling technique and will test in two different surface (artificial turf and natural grass). The component of Speed and Agility were measured using 30 Meter Sprint Test and Zig Zag Agility Test was used respectively. Statistical analysis of the tests was conducted by using paired sample t-test. A set of data was recorded and been analyze. There was a significant different for the artificial turf and natural grass on speed at the value of 0.05 and for agility test at the value of 0.05 .Hence, it was concluded that artificial turf and natural grass show a differences on agility and speed.